2001
DOI: 10.1111/j.1741-3737.2001.00136.x
|View full text |Cite
|
Sign up to set email alerts
|

Children's Time With Fathers in Intact Families

Abstract: This paper uses the Panel Study of Income Dynamics to examine children's involvement with their fathers in intact families as measured through time spent together. Our findings suggest that although mothers still shoulder the lion's share of the parenting, fathers' involvement relative to that of mothers appears to be on the increase. A ''new father'' role is emerging on weekends in intact families. Different determinants of fathers' involvement were found on weekdays and on weekends. Fathers' wages and work h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

45
666
10
46

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 790 publications
(784 citation statements)
references
References 32 publications
45
666
10
46
Order By: Relevance
“…This proportion is similar to, or slightly higher than (for fathers' proportion of child care), other reports in the literature; estimates vary depending on how involvement in child care is measured (Pleck, 1997;Yeung et al, 2001). …”
Section: Measures Child Caregiving Involvementmentioning
confidence: 70%
See 3 more Smart Citations
“…This proportion is similar to, or slightly higher than (for fathers' proportion of child care), other reports in the literature; estimates vary depending on how involvement in child care is measured (Pleck, 1997;Yeung et al, 2001). …”
Section: Measures Child Caregiving Involvementmentioning
confidence: 70%
“…For instance, the time-diary study mentioned above found that whereas older children spend less time with their fathers, the level of involvement with fathers relative to mothers increases with child age (Yeung et al, 2001). Fathers may feel more comfortable with older children who do not require as many gendered caregiving activities, such as diapering and bathing, as compared with younger children (Deutsch, Lussier, & Servis, 1993).…”
Section: Child Agementioning
confidence: 99%
See 2 more Smart Citations
“…Based on stereotypes of what mothering and fathering entail, it has been presumed that children need both a mother and father for appropriate psychological and sex-role development. Studies have shown that mothers spend more time interacting with children in a nurturing and care-giving role whilst fathering involves more breadwinning, stereotypically masculine tasks and play with children (Yeung 2001;Hawkins et al 2006;Lamb 2010). Thus the 'essential father' theory has evolved: boys need fathers to inhibit antisocial behaviour and develop appropriate masculine identities and girls need fathers to help deter promiscuity, teen pregnancy and substance abuse (Blankenhorn 1995;Popenoe 1996).…”
Section: The Importance Of Fathersmentioning
confidence: 99%